Tourist valorization of haymaking competitions in Serbia and surroundings - Bjeljac Željko; Brankov Jovana; Popović Ivan B. (Glasnik Srpskog Geografskog Društva, 2009)
Haymaking has always been the most important period for the existence of the population settled in the mountainous regions. There are numerous of competitions in haymaking organized at the meadows which present folklore, religion, customs and whole tradition of mountain regions of Serbia, Montenegro and Bosnia and Herzegovina. Specific ness of this events, completed with artistic and entertaining programs and connected with other social and geographical characteristics of the area of maintenance, present important part of total tourist offer. The work, according the economic and geographic criteria, separate competitions in haymaking of those which are strong enough and one that has the potential to become a leading force of destination and carrier of faster and better development of tourism. The aim of this paper is to assess the importance of this tourism events and to determine their rank.